Hierarchical and Heterogeneous Bioinspired Composites—Merging Molecular Self‐Assembly with Additive Manufacturing. Issue 28 (1st June 2017) - Rajasekharan, Anand K.; Bordes, Romain; Sandström, Carl; Ekh, Magnus; Andersson, Martin
Abstract : Biological composites display exceptional mechanical properties owing to a highly organized, heterogeneous architecture spanning several length scales. It is challenging to translate this ordered and multiscale structural organization in synthetic, bulk composites. Herein, a combination of top‐down and bottom‐up approach is demonstrated, to form a polymer‐ceramic composite by macroscopically aligning the self‐assembled nanostructure of polymerizable lyotropic liquid crystals via 3D printing. The polymer matrix is then uniformly reinforced with bone‐like apatite via in situ biomimetic mineralization. The combinatorial method enables the formation of macrosized, heterogeneous composites where the nanostructure and chemical composition is locally tuned over microscopic distances. This enables precise control over the mechanics in specific directions and regions, with a unique intrinsic–extrinsic toughening mechanism. As a proof‐of‐concept, the method is used to form large‐scale composites mimicking the local nanostructure, compositional gradients and directional mechanical properties of heterogeneous tissues like the bone‐cartilage interface, for mechanically stable osteochondral plugs. This work demonstrates the possibility to create hierarchical and complex structured composites using weak starting components, thus opening new routes for efficient synthesis of high‐performance materials ranging from biomaterials to structural nanocomposites. Abstract : A multiscale heterogeneous composite formed via combining bottom‐up self‐assembly, biomimetic mineralization, and top‐down additive manufacturing is reported. The composites are ordered constructs with an organic–inorganic interpenetrating nanostructure aligned over centimeter length‐scales, with structural features as small as 10 nm. The composites display a hierarchical structure, composition, and crack‐resist mechanics on similar length scales as biological materials like the bone‐cartilage composite.